KUALITAS PELAYANAN DAN STRATEGI PEMASARAN DALAM MENINGKATKAN PENJUALAN TOKO CAHAYA TANI ENREKANG - Haris, Abdul; Idris, Muhammad (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This study aims to analyze the influence of service quality and marketing strategy on sales improvement at Toko Cahaya Tani Enrekang. The research is based on the importance of enhancing service quality and implementing effective marketing strategies to boost sales performance. The study population consisted of 500 customers over the past six months, and using the Taro Yamane formula with a 10% precision level, a sample of 83 respondents was obtained. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS. The analysis produced the regression equation Y = 2.003 + 0.310X₁ + 0.440X₂ + e. The partial test (t-test) results indicated that both service quality (X₁) and marketing strategy (X₂) have a positive and significant effect on sales improvement (Y), while the simultaneous test (F-test) also showed that these two variables jointly have a significant influence on sales performance. The adjusted R-square value of 0.672 indicates that 67.2% of the variation in sales improvement is explained by service quality and marketing strategy, while the remaining 32.8% is influenced by other factors outside the study. Therefore, improving service quality and implementing appropriate marketing strategies play a crucial role in enhancing sales and strengthening the competitive advantage of Toko Cahaya Tani Enrekang.